Stand density of co‐existing species regulates above‐ground biomass along a local‐scale elevational gradient in tropical forests. Issue 2 (3rd April 2021) - Kunwar, Suwash; Wang, Li‐Qiu; Chaudhary, Rajeev; Joshi, Puspa Raj; Ali, Arshad
Abstract: Questions: (1) Do stand density, species diversity and individual tree size variation jointly increase above‐ground biomass (AGB) along an elevational gradient? (2) How does the local‐scale elevational gradient explain the variation in AGB directly and indirectly via stand density, species diversity facet and individual tree size variation? (3) What are the main ecological mechanisms explaining variation in AGB through joint effects of stand density, species diversity and individual tree size variation along an elevational gradient in tropical forests? We hypothesized that higher stand packing, and diverse and complex stand structure drive higher AGB along a local‐scale elevational gradient in tropical forests. Location: Western Nepal. Methods: We analyzed biophysical tree data from 101 tropical forest plots along an elevational gradient ranging from 218 to 1, 850 m above sea level. Structural equation models were applied to test the relationships among elevation, stand density, species diversity facet (either species richness, evenness, Shannon diversity or Simpson's dominance), tree diameter and height variation, and AGB. Results: Stand density increased but species diversity declined AGB, whereas tree diameter and height variation did not strongly influence AGB. The indirect effects of stand density, species diversity facet, and tree diameter and height variation on AGB via each other were non‐significant. Elevation reduced stand density, species richness and AGB but increased tree height variation, and hence, the indirect effects of elevation on AGB were variable. These results suggest that competitive exclusion or selection or environmental filtering effects are shaping the species diversity, structural complexity and AGB of the studied tropical forests. Conclusions: We argue that compact stand density, rather than diversity and individual tree size variation, of co‐existing species is important for higher AGB but higher species diversity and stand structural complexity may need to be considered in the context of biodiversity conservation and forest management. Abstract : Stand density, rather than the species diversity and individual tree size variation, of co‐existing species enhance above‐ground biomass along local‐scale elevational gradients in tropical forests, and hence, provide support for the selection, competitive exclusion and environmental filtering effects.